2021
DOI: 10.1111/1751-7915.13805
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas12a‐mediated genome engineering in the photosynthetic bacterium Rhodobacter capsulatus

Abstract: Purple non-sulfur photosynthetic bacteria (PNSB) such as Rhodobacter capsulatus serve as a versatile platform for fundamental studies and various biotechnological applications. In this study, we sought to develop the class II RNA-guided CRISPR/Cas12a system from Francisella novicida for genome editing and transcriptional regulation in R. capsulatus. Templatefree disruption method mediated by CRISPR/Cas12a reached ~90% editing efficiency when targeting ccoO or nifH gene. When both genes were simultaneously edit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…In E. coli , it was reported that zwf knockout led to an increased flux to the glycolytic pathway and tricarboxylic acid (TCA) cycle from glucose . Such a strategy has been adopted in both E. coli and R. sphaeroides , and the lycopene level was improved by 130% and 80%, respectively. , Recently, our group developed a CRSIPR/Cas12a-mediated genome editing tool via a template-free mechanism, and the disruption efficiency reached >90% . When compared to RcBIS6, the disruption of zwf by CRISPR/Cas12a (strain RcBIS7) increased the bisabolene titer up to 181.3 mg/L, which corresponds to a 91% improvement over that of the control (RcBIS6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In E. coli , it was reported that zwf knockout led to an increased flux to the glycolytic pathway and tricarboxylic acid (TCA) cycle from glucose . Such a strategy has been adopted in both E. coli and R. sphaeroides , and the lycopene level was improved by 130% and 80%, respectively. , Recently, our group developed a CRSIPR/Cas12a-mediated genome editing tool via a template-free mechanism, and the disruption efficiency reached >90% . When compared to RcBIS6, the disruption of zwf by CRISPR/Cas12a (strain RcBIS7) increased the bisabolene titer up to 181.3 mg/L, which corresponds to a 91% improvement over that of the control (RcBIS6).…”
Section: Resultsmentioning
confidence: 99%
“…The crRNA of zwf gene was amplified using pY001 (pFnCpf1_full, Addgene plasmid # 69975) as the template with primers LD0-U1-F/zwf-gRNA-R and then cloned into pBRucCas12a (CRISPR/Cas12a tool) through Golden-gate assembly to generate pBRucCas12a-zwf. The crRNAs of phbC , gltB , and gltD were amplified from pY001 with respective primers LD0-U1-F/phbC-gRNA-R, LD0-U2-F/gltB-gRNA-R, and LD0-U3-F/gltD-gRNA-R and then cloned into pBRucCas12a through Golden-gate assembly to generate pBRucCas12a-PGL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to concentrate on the effect of the genotype on the phenotypic observations, we checked which of the proteins from Table 2 are expressed at all at high organic nitrogen concentrations (Figure 4). Only the sigma-54 (σ 54 ) subunit of RNA-polymerase is both expressed under the conditions examined and the SNV exhibits a potential functional effect (Table 2).…”
Section: Transcriptome Analysismentioning
confidence: 99%
“…Template-free disruption method mediated by CRISPR/Cas12a developed for genome editing and transcriptional regulation in R. capsulatus with editing efficiency up to 90% would accelerate genetic construction of PNSB strains [147]. Considering the possibility that alternative nitrogenases in PNSB might efficiently supply hydrogen, a substrate for respiration to reduce oxygen concentration under microaerobic conditions, mutations in vnfA, anfA, or both vnfA and anfA that have the coded proteins adopt their active conformations may be important for efficiently producing hydrogen in the presence of ammonium.…”
Section: Genetic Engineering Of Pnsb To Modify Regulation Of Nitrogen...mentioning
confidence: 99%